2006
DOI: 10.4161/auto.3089
|View full text |Cite
|
Sign up to set email alerts
|

Causal Links Between Protein Folding in the ER and Events Along the Secretory Pathway

Abstract: The 70-kDa heat shock protein (Hsp70) family comprises the most abundant and important group of molecular chaperones. Hsp70s cooperate with a number of cofactors, which define their functions. We recently reported that a yeast protein, Rot1, is a putative cofactor of BiP, an endoplasmic reticulum (ER)-localized Hsp70. Rot1 is an essential ER membrane protein and may be involved in protein folding. Mutation of the ROT1 gene caused defects in cell wall synthesis and lysis of autophagic bodies. We suggest that Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…, encoding an essential ER-localized membrane protein, was initially reported as a gene required for ß-1,6-glucan synthesis (Bickle et al 1998;Machi et al 2004). Mutations of ROT1 cause pleiotropic defects in cell wall synthesis, cytoskeleton dynamics, or in lysis of autophagic bodies (Takeuchi et al 2006a;Takeuchi et al 2006b). More recently it was demonstrated that Rot1 can function as a general chaperone exhibiting anti-aggregation activity in vitro, and in vivo the rot1-2 mutation caused an accelerated degradation of several proteins of the secretory pathway via ER-associated degradation (Takeuchi et al 2008).…”
Section: Rot1mentioning
confidence: 99%
“…, encoding an essential ER-localized membrane protein, was initially reported as a gene required for ß-1,6-glucan synthesis (Bickle et al 1998;Machi et al 2004). Mutations of ROT1 cause pleiotropic defects in cell wall synthesis, cytoskeleton dynamics, or in lysis of autophagic bodies (Takeuchi et al 2006a;Takeuchi et al 2006b). More recently it was demonstrated that Rot1 can function as a general chaperone exhibiting anti-aggregation activity in vitro, and in vivo the rot1-2 mutation caused an accelerated degradation of several proteins of the secretory pathway via ER-associated degradation (Takeuchi et al 2008).…”
Section: Rot1mentioning
confidence: 99%
“…In eukaryotic cells, intracellular degradation of mutated proteins was known to depend on two main proteolytic pathways: endoplasmic reticulum (ER) associated degradation through proteasomes or autophagy through lysosomes . Most secretory proteins enter the ER to undergo posttranslational modifications and folding prior to their transit to the Golgi and subsequently to the cell surface . Misfolded proteins were retained within the ER lumen permanently or were transported to the cytosol in a retrograde manner and eventually degraded through proteasomes .…”
Section: Introductionmentioning
confidence: 99%